Non‐overt disseminated intravascular coagulopathy associated with the first obinutuzumab administration in patients with chronic lymphocytic leukemia. Issue 3 (3rd February 2021) - Fresa, Alberto; Autore, Francesco; Innocenti, Idanna; Piciocchi, Alfonso; Tomasso, Annamaria; Morelli, Francesca; Sorà, Federica; Sica, Simona; De Stefano, Valerio; Laurenti, Luca
Abstract: Infusion‐related reactions are among the worst complications of obinutuzumab (G) administration and occur predominantly during the first infusion. We reported another adverse event related to the first G infusion, a subclinical coagulopathy. We retrospectively analyzed a cohort of 13 pts with chronic lymphocytic leukemia treated with a frontline G‐chlorambucil regimen. Six pts developed non‐overt disseminated intravascular coagulopathy (DIC) (46%) after the first administration of G. The coagulopathy was subclinical and self‐limited in all pts, not requiring any intervention apart from the suspension of anticoagulant therapy in one pt. We observed a drop in the platelet count, an elevation of D‐dimer levels, and an elongation of activated partial thromboplastin time. We found a significant difference in the platelet count between the pts with DIC and those withouts; in fact, all the six pts with non‐overt DIC had a platelet count greater than 100 × 10 9 /L, while in the other group only one ( p = 0.019). A trend towards a lower lymphocyte count and a higher CD20 expression was found in the pts with DIC. No other correlation between the DIC complication and the clinical or laboratory characteristics of the patients was found. The pathogenesis of the G‐related non‐overt DIC could be related to the consumption of the platelets after the lysis of lymphocytes, probably triggered by the damage associated molecular patterns. Despite its limitations, this study describes a new adverse event and identifies a specific subgroup of patients whose clinical management at the time of the infusion of G may need to be refined.